Manajemen strategi dalam pengembangan dan keberhasilan perbankan syariah - Attamimi, Inas (Maliki Interdisciplinary Journal, 2025)
Strategic management plays an important role in the growth and development of Islamic banks. In Indonesia, Islamic banks operate based on Sharia principles regulated by the DSN MUI and Law No. 21 of 2008. This study explores the concept of strategic management and its application in Islamic banks, covering basic principles, competitors, and the use of SWOT analysis as a tool to identify internal and external factors. The results of this analysis indicate that the strengths of Islamic banks lie in product innovation, service quality, and supervision by the Sharia Supervisory Board. However, weaknesses such as technological limitations and human resources were also found. Opportunities for growth include support from regulations and increased public awareness, while threats come from competition between banks and suboptimal public understanding. Effective marketing strategies utilizing SWOT analysis can increase competitiveness and the sustainable development of Islamic banks. This study recommends that Islamic banks continue to improve risk management and develop products in accordance with Islamic principles to face challenges and take advantage of opportunities in the market.